Constructing an episode of care from acute hospitalization records for studying effects of timing of hip fracture surgery. Issue 2 (11th August 2015) - Sheehan, Katie J.; Sobolev, Boris; Guy, Pierre; Bohm, Eric; Hellsten, Erik; Sutherland, Jason M.; Kuramoto, Lisa; Jaglal, Susan; ,
ABSTRACT: Episodes of care defined by the event of hip fracture surgery are widely used for the assessment of surgical wait times and outcomes. However, this approach does not consider nonoperative deaths, implying that survival time begins at the time of procedure. This approach makes treatment effect implicitly conditional on surviving to treatment. The purpose of this article is to describe a novel conceptual framework for constructing an episode of hip fracture care to fully evaluate the incidence of adverse events related to time after admission for hip fracture. This admission‐based approach enables the assessment of the full harm of delay by including deaths while waiting for surgery, not just deaths after surgery. Some patients wait until their conditions are optimized for surgery, whereas others have to wait until surgical service becomes available. We provide definitions, linkage rules, and algorithms to capture all hip fracture patients and events other than surgery. Finally, we discuss data elements for stratifying patients according to administrative factors for delay to allow researchers and policymakers to determine who will benefit most from expedited access to surgery. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:197–204, 2016.